Prescription of quadruple therapy in heart failure with reduced ejection fraction during hospitalization - Ibrahim Hatoum (Bulletin of the National Research Centre, 2024)
Abstract Background Hospitalization of patients with heart failure makes it possible to optimize drug therapy, considerably improving the prognosis of this serious condition. Methods We conducted a retrospective descriptive study of patients with reduced left ventricular ejection fraction (≤ 40%) in the Cardiology Department of a community hospital center in France to measure the prescription rate of heart failure medications in hospitalized patients with reduced ejection fraction heart failure and identify their limiting factors. The primary endpoint was the prescription on the discharge prescription of the following four drug classes: beta-blockers, renin–angiotensin–aldosterone system blockers, mineralocorticoid receptor antagonists, and sodium-glucose co-transporter inhibitors. Results From September 1, 2022, to March 31, 2023, 73 patients were included in the study. About one-third of patients were discharged with the recommended four drug classes. Those discharged with all 4 drug classes were younger and had preserved renal function. Conclusions The low rate of prescription of heart failure medications after hospitalization is a reminder of the need to develop a specialized follow-up structure to optimize the drug treatment of reduced ejection fraction heart failure, even in the most fragile patients.